Adjusting Degree of Modification and Composition of gelAGE-Based Hydrogels Improves Long-Term Survival and Function of Primary Human Fibroblasts and Endothelial Cells in 3D Cultures - Genc, Hatice; Cianciosi, Alessandro; Lohse, Raphael; Stahlhut, Philipp; Groll, Jurgen; Alexiou, Christoph; Cicha, Iwona; Juengst, Tomasz (Biomacromolecules, 2023)
This study aimed to develop a suitable hydrogel-based 3D platform to support long-term culture of primary endothelial cells (ECs) and fibroblasts. Two hydrogel systems based on allyl-modified gelatin (gelAGE), G1MM and G2LH, were cross-linked via thiol-ene click reaction with a four-arm thiolated polyethylene glycol (PEG-4-SH). Compared to G1MM, the G2LH hydrogel was characterized by the lower polymer content and cross -linking density with a softer matrix and homogeneous and open porosity. Cell viability in both hydrogels was comparable, although the G2LH-based platform supported better F-actin organization, cell- cell interactions, and collagen and fibronectin production. In co -cultures, early morphogenesis leading to tubular-like structures was observed within 2 weeks. Migration of fibroblasts out of spheroids embedded in the G2LH hydrogels started after 5 days of incubation. Taken together, the results demonstrated that the G2LH hydrogel fulfilled the demands of both ECs and fibroblasts to enable long-term culture and matrix remodeling.
CRIS-Team WoS Importer:2023-03-17

A Print-and-Fuse Strategy for Sacrificial Filaments Enables Biomimetically Structured Perfusable Microvascular Networks with Functional Endothelium Inside 3D Hydrogels - Ryma, Matthias; Genc, Hatice; Nadernezhad, Ali; Paulus, Ilona; Schneidereit, Dominik; Friedrich, Oliver; Andelovic, Kristina; Lyer, Stefan; Alexiou, Christoph; Cicha, Iwona; Groll, Juergen (Advanced Materials, 2022)
A facile and flexible approach for the integration of biomimetically branched microvasculature within bulk hydrogels is presented. For this, sacrificial scaffolds of thermoresponsive poly(2-cyclopropyl-2-oxazoline) (PcycloPrOx) are created using melt electrowriting (MEW) in an optimized and predictable way and subsequently placed into a customized bioreactor system, which is then filled with a hydrogel precursor solution. The aqueous environment above the lower critical solution temperature (LCST) of PcycloPrOx at 25 degrees C swells the polymer without dissolving it, resulting in fusion of filaments that are deposited onto each other (print-and-fuse approach). Accordingly, an adequate printing pathway design results in generating physiological-like branchings and channel volumes that approximate Murray's law in the geometrical ratio between parent and daughter vessels. After gel formation, a temperature decrease below the LCST produces interconnected microchannels with distinct inlet and outlet regions. Initial placement of the sacrificial scaffolds in the bioreactors in a pre-defined manner directly yields perfusable structures via leakage-free fluid connections in a reproducible one-step procedure. Using this approach, rapid formation of a tight and biologically functional endothelial layer, as assessed not only through fluorescent dye diffusion, but also by tumor necrosis factor alpha (TNF-alpha) stimulation, is obtained within three days.
CRIS-Team WoS Importer:2022-06-17

Differential responses to bioink‐induced oxidative stress in endothelial cells and fibroblasts - Genc, Hatice; Hazur, Jonas; Karakaya, Emine; Dietel, Barbara; Bider, Faina; Groll, Jürgen; Alexiou, Christoph; Boccaccini, Aldo R.; Detsch, Rainer; Cicha, Iwona (International Journal of Molecular Sciences, 2021)
A hydrogel system based on oxidized alginate covalently crosslinked with gelatin (ADA‐ GEL) has been utilized for different biofabrication approaches to design constructs, in which cell growth, proliferation and migration have been observed. However, cell–bioink interactions are not completely understood and the potential effects of free aldehyde groups on the living cells have not been investigated. In this study, alginate, ADA and ADA‐GEL were characterized via FTIR and NMR, and their effect on cell viability was investigated. In the tested cell lines, there was a concen-tration‐dependent effect of oxidation degree on cell viability, with the strongest cytotoxicity observed after 72 h of culture. Subsequently, primary human cells, namely fibroblasts and endothelial cells (ECs) were grown in ADA and ADA‐GEL hydrogels to investigate the molecular effects of oxidized material. In ADA, an extremely strong ROS generation resulting in a rapid depletion of cellular thiols was observed in ECs, leading to rapid necrotic cell death. In contrast, less pronounced cytotoxic effects of ADA were noted on human fibroblasts. Human fibroblasts had higher cellular thiol content than primary ECs and entered apoptosis under strong oxidative stress. The presence of gelatin in the hydrogel improved the primary cell survival, likely by reducing the oxidative stress via binding to the CHO groups. Consequently, ADA‐GEL was better tolerated than ADA alone. Fibroblasts were able to survive the oxidative stress in ADA‐GEL and re‐entered the proliferative phase. To the best of our knowledge, this is the first report that shows in detail the relationship between oxidative stress‐induced intracellular processes and alginate di‐aldehyde‐based bioinks.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Alginate di‐aldehyde; Cell death; Cell viability; Gelatin; Glutathione; Oxidative stress

Effect of a single immersion in cold water below 4 °C on haemorheological properties of blood in healthy men - Teległów, Aneta; Genc, Hatice; Cicha, Iwona (Scientific Reports, 2024)
Cold water immersion (CWI) involves rapid cooling of the body, which, in healthy individuals, triggers a defence response to an extreme stimulus, to which the body reacts with stress. The aim of the study was to determine the effect of CWI on hemorheological blood indicators. The study group consisted of 13 young males. Blood samples were collected before and after CWI. The assessed parameters included the complete blood count, fibrinogen, hs-C-reactive protein (CRP), proteinogram, and blood rheology factors, such as erythrocyte elongation index (EI), half-time of total aggregation, and aggregation index. Additionally, the effect of reduced temperature on primary human vascular endothelium was investigated in vitro. CWI resulted in the decrease of body temperature to 31.55 ± 2.87 °C. After CWI, neutrophil count and mean corpuscular volume (MCV) were significantly increased in the study group, while lymphocyte count was significantly decreased. Significantly higher levels of total blood protein and albumin concentration were detected after the immersion. Among hemorheological characteristics, erythrocyte EIs at shear stress values ranging from 2.19 to 60.30 Pa were significantly lower after CWI. No significant changes in other rheological, morphological or biochemical parameters were observed. In vitro, human umbilical vein endothelial cells responded to 3 h of temperature decrease to 25 °C with unchanged viability, but increased recruitment of THP-1 monocytic cells and changes in cell morphology were observed. This was the first study to evaluate the effect of single CWI on rheological properties of blood in healthy young men. The results indicate that a single CWI may increase blood protein concentrations and worsen erythrocyte deformability parameters.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Blood rheology; Cold water immersion (CWI); Endothelial cells; Erythrocytes; Low temperature

Endothelialization of Whey Protein Isolate-Based Scaffolds for Tissue Regeneration - Genc, Hatice; Friedrich, Bernhard; Alexiou, Christoph; Pietryga, Krzysztof; Cicha, Iwona; Douglas, Timothy E.L. (Molecules, 2023)
Background: Whey protein isolate (WPI) is a by-product from the dairy industry, whose main component is β-lactoglobulin. Upon heating, WPI forms a hydrogel which can both support controlled drug delivery and enhance the proliferation and osteogenic differentiation of bone-forming cells. This study makes a novel contribution by evaluating the ability of WPI hydrogels to support the growth of endothelial cells, which are essential for vascularization, which in turn is a pre-requisite for bone regeneration. Methods: In this study, the proliferation and antioxidant levels in human umbilical vascular endothelial cells (HUVECs) cultured with WPI supplementation were evaluated using real-time cell analysis and flow cytometry. Further, the attachment and growth of HUVECs seeded on WPI-based hydrogels with different concentrations of WPI (15%, 20%, 30%, 40%) were investigated. Results: Supplementation with WPI did not affect the viability or proliferation of HUVECs monitored with real-time cell analysis. At the highest used concentration of WPI (500 µg/mL), a slight induction of ROS production in HUVECs was detected as compared with control samples, but it was not accompanied by alterations in cellular thiol levels. Regarding WPI-based hydrogels, HUVEC adhered and spread on all samples, showing good metabolic activity. Notably, cell number was highest on samples containing 20% and 30% WPI. Conclusions: The demonstration of the good compatibility of WPI hydrogels with endothelial cells in these experiments is an important step towards promoting the vascularization of hydrogels upon implantation in vivo, which is expected to improve implant outcomes in the future.
CRIS-Team Scopus Importer:2023-11-10
Keywords: 3D cell seeding; endothelial cell compatibility; hydrogels; thiol levels; tubular scaffolds; whey protein

Melt Electrowriting of Isomalt for High-Resolution Templating of Embedded Microchannels - Nadernezhad, Ali; Ryma, Matthias; Genc, Hatice; Cicha, Iwona; Jüngst, Tomasz; Groll, Jürgen (Advanced Materials Technologies, 2021)
Fabrication of microchannels using 3D printing of sugars as fugitive material is explored in different fields, including microfluidics. However, establishing reproducible methods for the controlled production of sugar structures with sub-100 μm dimensions remains a challenge. This study pioneers the processing of sugars by melt electrowriting (MEW) enabling the fabrication of structures with so far unprecedented resolution from Isomalt. Based on a systematic variation of process parameters, fibers with diameters down to 20 μm can be fabricated. The flexibility in the adjustment of fiber diameter by on-demand alteration of MEW parameters enables generating constructs with perfusable channels within polydimethylsiloxane molds. These channels have a diameter that can be adjusted from 30 to 200 μm in a single design. Taken together, the experiments show that MEW strongly benefits from the thermal and physical stability of Isomalt, providing a robust platform for the fabrication of small-diameter embedded microchannel systems.
CRIS-Team Scopus Importer:2021-07-02
Keywords: embedded templating; melt electrowriting; microfibers; microfluidics; sacrificial printing; sugar glass printing

On-Demand Drug Delivery: Recent Advances in Cardiovascular Applications - Genc, Hatice; Efthimiadou, Eleni; Cicha, Iwona (Frontiers in Drug Delivery, 2022)
Cardiovascular diseases (CVD), including life-threatening atherosclerosis and arterial thrombosis, account for almost 50% of all deaths in Europe and around 30% of all deaths worldwide. Despite the ongoing improvement and accessibility of invasive cardiovascular interventions and pharmacological therapies, pathological processes often progress asymptomatically, before manifesting themselves as unstable angina pectoris, myocardial infarction, sudden cardiac death or stroke. Since atherosclerosis and thrombosis represent localized disease processes, insufficient response to systemically-administered drugs is a common problem. The available pharmacological therapies are often burdened by poor tolerability, limited efficacy and/or bioavailability. Although encapsulating drugs in a nanoscale shell increases their circulation time and availability, it does not guarantee disease-specific targeting, or the proper control of the drug release. In contrast, on-demand drug delivery has the advantage of localized treatment and allows reducing off-target effects by a stimuli-controlled drug release in the affected region. Such “smart” systems are expected to have a great therapeutic potential in CVD. This mini-review article highlights recent advances in stimuli-responsive drug delivery approaches to CVD, with specific drug release triggered either internally or externally.
CRIS-Team Scopus Importer:2025-07-10
Keywords: atherosclerosis; biosensing drug carriers; ischemia-reperfusion; light-activated drugs; smart drug delivery; stimuli-responsive drug release; stroke; thrombosis

Polydopamine and gelatin coating for rapid endothelialization of vascular scaffolds - Kopeć, Kamil; Wojasiński, Michał; Eichler, Mathis; Genc, Hatice; Friedrich, Ralf P.; Stein, René; Singh, Raminder; Alexiou, Christoph; Hlawaty, Hanna; Ciach, Tomasz; Cicha, Iwona (Materials Science and Engineering C, 2021)
Rapid endothelialization helps overcome the limitations of small-diameter vascular grafts. To develop biomimetic non-thrombogenic coatings supporting endothelialization, medical-grade polyurethane (PU) nanofibrous mats and tubular scaffolds with a diameter below 6 mm prepared by solution blow spinning were coated with polydopamine (PDA), or PDA and gelatin (PDA/Gel). The scaffolds were characterized by scanning electron microscopy, porosity measurement, tensile testing, wettability, Fourier Transform Infrared spectroscopy, and termogravimetric analysis, followed by the measurement of coating stability on the tubular scaffolds. The effect of coating on scaffold endothelialization and hemocompatibility was evaluated using human umbilical vein endothelial cells (HUVECs) and human platelets, showing low numbers of adhering platelets and significantly higher numbers of HUVECs on PDA- and PDA/Gel-coated mats compared to control samples. Tubular PU scaffolds and commercial ePTFE prostheses coated with PDA or PDA/Gel were colonized with HUVECs using radial magnetic cell seeding. PDA/Gel-coated samples achieved full endothelial coverage within 1–3 days post-endothelialization. Altogether, PDA and PDA/Gel coating significantly enhance the endothelialization on the flat surfaces, tubular small-diameter scaffolds, and commercial vascular prostheses. The presented approach constitutes a fast and efficient method of improving scaffold colonization with endothelial cells, expected to work equally well upon implantation.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Human endothelial cell; Magnetic cell seeding; Polydopamine coating; Polyurethane scaffolds; Tubular grafts

The Effect of Antibacterial Particle Incorporation on the Mechanical Properties, Biodegradability, and Biocompatibility of PLA and PHBV Composites - Mazur, Karolina; Singh, Raminder; Friedrich, Ralf P.; Genc, Hatice; Unterweger, Harald; Sałasińska, Kamila; Bogucki, Rafał; Kuciel, Stanisław; Cicha, Iwona (Macromolecular Materials and Engineering, 2020)
The composites based on polylactide (PLA) and poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) with the addition of antibacterial particles: silver (Ag) and copper oxide (CuO) are characterized. Basic mechanical properties and biodegradation processes, as well as biocompatibility of materials with human cells are determined. The addition of Ag or CuO to the polymers do not significantly affect their mechanical properties, flammability, or biodegradation rate. However, several differences between the base materials are observed. PLA-based composites have higher tensile and impact strength values, while PHBV-based ones have a higher modulus of elasticity, as well as better mechanical properties at elevated temperatures. Concerning biocompatibility, each of the tested materials support the growth of fibroblasts over time, although large differences are observed in the initial cell attachment. The analysis of hydrolytic degradation effects on the structure of materials shows that PHBV degrades much faster than PLA. The results of this study confirm the good potential of the investigated biodegradable polymer composites with antibacterial particles for future biomedical applications.
CRIS-Team Scopus Importer:2020-08-14
Keywords: biocompatibility; biocomposites; copper oxide particles; poly (3-hydroxybutyrate-co-3-hydroxyvalerate); polylactide; silver particles